2013
DOI: 10.1111/iju.12185
|View full text |Cite
|
Sign up to set email alerts
|

Nocturia and sleep quality after transurethral resection of the prostate

Abstract: Abbreviations & AcronymsObjectives: To evaluate the clinical efficacy of transurethral resection of the prostate on nocturia and sleep disorders in patients with lower urinary tract symptoms suggestive of benign prostatic obstruction. Methods: A prospective multicenter study including lower urinary tract symptoms suggestive of benign prostatic obstruction patients with nocturia (twice or more) undergoing transurethral resection of the prostate was carried out. All patients were assessed using the International… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
13
0
2
Order By: Relevance
“…In addition, nocturia is strongly associated with benign prostatic hyperplasia (BPH) and nocturnal polyuria . Wada et al, in a small study, investigated whether TURP could improve nocturia and sleep disorders in patients with LUTS/BPO undergoing TURP. According to their results, nocturia score showed the least improvement among the seven subscores of IPSS, however in this study, nocturia severity was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nocturia is strongly associated with benign prostatic hyperplasia (BPH) and nocturnal polyuria . Wada et al, in a small study, investigated whether TURP could improve nocturia and sleep disorders in patients with LUTS/BPO undergoing TURP. According to their results, nocturia score showed the least improvement among the seven subscores of IPSS, however in this study, nocturia severity was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature [5], we estimated that 74 patients will need to be recruited in order to detect a clinically significant difference of 25% between the 2 groups (with a power of 80%). Based on past clinical trial experience, we estimated that 20% of randomized participants will be lost in follow up, therefore 88 patients will need to be recruited, and 170 participants who will complete the item in our study.…”
Section: Methodsmentioning
confidence: 99%
“…So könnte die Deobstruktion der Prostata als ultima ratio auch zur Behandlung der Nykturie bei persistierenden LUTS angesehen werden. Obwohl die Nykturiefrequenz mit einer TURP signifikant gesenkt werden kann, in einer Untersuchung mit 49 Patienten von durchschnittlich 3,0 ± 1,2 auf 1,9 ± 0,8 Mal pro Nacht [29] und in einer anderen Untersuchung mit 56 Patienten von 3,4 ± 1,2 auf 2,6 ± 0,99 pro Nacht [30], ist die Nykturie das am häufigsten persistierende Einzelsymptom nach TURP [22]. In einer dänischen Untersuchung mit 62 Patienten lag bei 50 % der mit TURP behandelten Männer auch noch 5 Jahre nach der Operation eine Nykturie vor [31].…”
Section: Chirurgische Therapieunclassified
“…In einer dänischen Untersuchung mit 62 Patienten lag bei 50 % der mit TURP behandelten Männer auch noch 5 Jahre nach der Operation eine Nykturie vor [31]. Die TURP kann aber bei der Mehrheit der Patienten die Schlaf-und Lebensqualität verbessern und die ungestörte Schlafzeit signifikant, wenn auch nur um weniger als 1 Stunde verlängern [29,30]. Die persistierende Schlafstörung nach TURP war in einer Untersuchung mit der Persistenz von Blasenspeicher-und Blasenentleerungssymptomen assoziiert [29].…”
Section: Chirurgische Therapieunclassified